Diseño textil con la técnica del macramé para la aplicación en indumentaria - Lasluisa Sánchez, Shirley Monserrath (2024)
In this integrative project, he proposes the creation of a textile design made with cotton threads using the macramé technique, analyzing each type of knot to then determine innovative textile designs for application in clothing seeking to merge the traditional with modern fashion trends. It seeks to explore the integration of this ancient knotting technique into contemporary fashion. The project involves the investigation of the macramé technique through a literature review through theoretical foundations such as: its historical context as a craft and material, the identification of the types of knots can be adapted to textile design and the application of clothing. The main objective of the project, based on the experimentation of adapting the macramé technique, the characteristics and finishes of the knots in each of the fabrics and fibers used were observed, the type of yarn that is the most appropriate for the development of the textile was obtained, it is the cotton thread in macramé in thickness of 3mm since the thread is suitable for making the knots and that the textile is not too heavy or thick. The project is carried out in order to contribute to culture and craftsmanship through a textile catalogue applying the different types of basic knots and a combination of knots such as: the flat knot, the festoon knot, the lark knot, etc.; It was based on the experimentation sheets as a result of the interpretation of the interview and the focus group carried out. In addition, the final textile design identifies the opportunities and challenges of incorporating macramé into textile production